Effect of Porosity and Permeability Evolution on Injection‐Induced Aseismic Slip. Issue 7 (28th June 2021) - Yang, Yuyun; Dunham, Eric M.
Abstract: It is widely recognized that fluid injection can trigger aseismic fault slip. However, the processes by which the fluid‐rock interactions facilitate or inhibit slip are poorly understood and some are oversimplified in most models of injection‐induced slip. In this study, we perform a 2D anti‐plane shear investigation of aseismic slip that occurs in response to fluid injection into a permeable fault governed by rate‐and‐state friction. We account for porosity and permeability changes that accompany slip, including dilatancy, and quantify how these processes affect pore pressure diffusion, which couples to aseismic slip. Fault response to injection has two phases. In the first phase, slip is negligible and pore pressure closely follows the standard linear diffusion model. Pressurization eventually triggers aseismic slip close to the injection site. In the second phase, aseismic slip front expands outward and dilatancy causes pore pressure to depart from the linear diffusion model. We quantify how prestress, injection rate, permeability and other fluid transport properties affect the slip front migration rate, finding rates ranging from 10 to 1, 000 m/day for typical parameters. The migration rate is strongly influenced by the fault's closeness to failure and injection rate. The total slip on the fault, on the other hand, is primarily determined by the injected volume, with minimal sensitivity to injection rate. Additionally, we show that when dilatancy is neglected, slip front migration rate and total slip can be several times higher. Our modeling demonstrates that porosity and permeability evolution, especially dilatancy, fundamentally alters how faults respond to fluid injection. Plain Language Summary: The underground injection of fluids during wastewater disposal, geothermal operations, and other energy‐production activities has been linked to the occurrence of earthquakes. In addition to earthquakes, fluid injection can also trigger aseismic slip on faults, that is, frictional sliding that occurs so slowly that seismic waves and ground shaking are not produced. Here, we perform computer modeling of fluid injection and aseismic slip, exploring how the injection rate and fluid transport properties influence the aseismic slip response. We speculate that additional complexity in frictional properties and other conditions would cause aseismic slip to be accompanied by numerous, small earthquakes (microseismicity), as is often observed during injection. We quantify the rate at which aseismic slip migrates outward from the injection site and compare predicted migration rates to observed microseismicity patterns. Our model also predicts fluid pressure changes, slip, rock deformation surrounding the fault, and fluid flow paths that might be measurable and used to validate the modeling. Key Points: Modeling of constant rate fluid injection into a fault predicts steadily propagating aseismic slip front Migration rate of aseismic slip front increases with injection rate and ranges from 10 to 1, 000 m/day for typical parameters Dilatancy and permeability enhancement alter system response as compared to linear pore pressure diffusion